Analisis Penerapan Sistem Informasi Manajemen terhadap Kinerja Pegawai Usaha Daster Dasby’D - Veni Gerhana Putri; Anissa Aprilia Dewanti; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research was conducted with the aim of being able to find out what it looks like and how the effect of implementing a management information system on the performance of Dasby'D employees. This research was conducted through a survey related to the use of management information systems on the performance of employees. The method carried out was observation and interviews with respondents (Dasby'D employees). Based on the results of the research conducted, it is stated that if the management information system is implemented, it will have a significant effect on the performance of Dasby'D business employees. Based on qualitative data that describes that a leader who is firm and has good communication to implement an organized and good management information system can have a significant effect on the performance of employees. This can be known by the results of interviews and observations where they state that they will feel enthusiastic about working if they have a boss who can give clear and appropriate directions and can provide support to employees so that employees can be motivated to work better and later will also have a significant effect on the sales produced.